Creedal Nationalism in early American labor movements - Smith, Brian G. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the United States during the late 1820s, the labor movements formed that faced public accusations of being un-American and potentially puppets of European influence. These accusations often came from politicians or organizations sympathetic to ethnic nationalism. Partially in response to these charges, labor movements began to espouse versions of Creedal Nationalism.
Keywords: American nationalism; creedal nationalism; Labor Unions; American political development